Aggregate demand and the slowdown of Brazilian economic growth in 2011-2014 - Serrano, Franklin; Summa, Ricardo (Nova Economia, 2016)
This paper looks in detail at the sharp slowdown in the Brazilian economy for the years 2011-2014. We argue that the slowdown is overwhelmingly the result of a sharp decline in domestic demand, rather than a fall in exports and even less any change in external financial conditions. The sharp fall in domestic demand, in turn, is shown to be a result of deliberate policy decisions made by the government and was not necessary, i.e., it was not made in response to some external constraint such as a balance-of-payments problem.